Globalization's bystanders: Does trade liberalization hurt countries that do not participate? - Alan V. Deardorff; Robert M. Stern (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper uses trade theory to examine the effects of trade liberalization on countries that do not participate in it. These include both countries that fail to participate in multilateral trade negotiations, and also countries that lie outside of preferential trading arrangements such as free trade areas. The analysis suggests that, while it is theoretically possible for excluded countries to gain, through improved terms of trade, from trade liberalization, several reasons suggest that they are more likely to lose. – globalization ; trade liberalization
Keywords: F13; 330; Außenhandelsliberalisierung; Globalisierung; Wohlfahrtseffekt; Außenhandelspräferenz; Welt